Teacher leadership as a key element for enhancing teacher professional development - Flores, Maria Assunção (2018)
This paper reports on findings from a 3-year research project aimed at examining teachers’ views of teacher leadership and the conditions to enhance it. A mixed-method research design was devised. Data were collected in three phases; i) phase I consisted of a national survey in which 2702 teachers participated; ii) phase II included semi-structured interviews with the 11 head teachers and focus group with pupils (n=108) and with teachers (n=99); and iii) phase III involved a professional development programme in 5 schools located in northern Portugal, in which 66 teachers participated. Findings point to three main themes: i) a pluralistic view of leadership; ii) teachers as leaders of learning; iii) developing school-based projects as an opportunity for professional development. Implications for developing conditions for teacher leadership and professional development are discussed.